Sistem Penjualan Point of Sale Berbasis Web Pada Toko Bangunan - Rendy, Rendy Alamsyah; Deny Sundari (Journal of Computing and Informatics Research, 2023)
Easy Jaya Building Store is a building shop that sells various kinds of tools and building material supplies. This shop is located on Jalan Cristophel Mihing No 123 and has been established since 2017. Based on the process the business that is currently running at the store that becomes an obstacle is when making notes, checking prices of goods and stock of goods. In overcoming this problem, a Point Of Sale sales system was created so that problems that arise such as making notes, prices of goods and stock of goods are more structured and more detailed which will certainly make it easier in the store. Based on the results of the trial of this program which has been implemented at the Easy Jaya Building Store, the results obtained are very good and also received a good response from the shop owner because the program created has been very helpful. As for suggestions in its development such as adding accounting, barcode scanners and also making the user interface look even better